Are extension requests an opportunity to support student self-management skills?. Issue 2 (17th February 2019) - Stallman, Helen; Muncey, Patricia
ABSTRACT: Self-regulation, self-management, and coping skills are essential personal attributes for social work graduates who often work with clients with complex and traumatic histories. This study explored self-management skills in students applying for extensions of time to complete assignments. Participants were 117 students enrolled in a second-year undergraduate social work subject. Requests were analyzed in two ways: (1) did the request meet the university policy criteria for approval; and (2) thematic analysis of requests that did not meet criteria to identify the reasons students were providing to support their request. A quarter of students in the course applied for an extension. The overwhelming majority of requests did not meet the university's policy criteria for approval, with only two having a valid reason and the required documentation. The primary reason for extension requests in this cohort was poor self-management skills, specifically time-management and coping. Despite not meeting university policy requirements, all requests were approved. The results from this study confirm that most students applying for extension requests are not eligible for an extension. The reasons provided demonstrate problems coping with course requirements because of self-management problems. Implications for supporting students and staff are discussed.